Dampak Kampung Budaya Majapahit pada Karakteristik Sosial Masyarakat Desa Bejijong - Febrina Nur Rahmi Briliana (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Majapahit culture has influenced the social characteristics of the people living in the Majapahit Cultural Village, Bejijong Village. The influence of the Majapahit Cultural Village has encouraged the community to live alongside Majapahit Culture. This research aims to identify the impact of the construction of the Majapahit Cultural Village on the social characteristics of the Bejijong Village community. This research used Emile Durkheim's theory of social change and Sorokin and Zimmerman's theory of village characteristics. The method used is qualitative descriptive with data search methods from primary surveys in interviews, field observations, questionnaires, and secondary data from literature studies. In the preliminary survey, interviews were conducted with Pokdarwis, the Head of Bejijong Village, and the Department of Culture, Youth, Sports and Tourism (DISBUDPORAPAR) of Mojokerto Regency, and a questionnaire was filled in by determining respondents using purposive sampling and the Slovin formula to obtain 44 respondents. There are two research variables, namely demographic and environmental impacts, with six indicators: population size, livelihoods, population density, social stratification, environment, social interaction, and social solidarity. This research was conducted in 2023, but the data is periodic from 2018 to 2022. The results of this research show that the existence of the Majapahit Cultural Village has had a demographic impact in the form of an increase in population, an increase in population density values, and a change in livelihood from being a farmer to being a farmer. I have other jobs in entrepreneurship, establishing tourism awareness groups, and increasing mobility. The ecological impact is that the building has a Majapahit architectural identity, and the community's mindset becomes more open regarding technology and its potential, preserving Majapahit culture.